1997
DOI: 10.1016/s0014-5793(97)00688-1
|View full text |Cite
|
Sign up to set email alerts
|

Lithium inhibits Alzheimer's disease‐like tau protein phosphorylation in neurons

Abstract: In Alzheimer's disease, tau protein becomes hyperphosporylated, which can contribute to neuronal degeneration. However, the implicated protein kinases are still unknown. Now we report that lithium (an inhibitor of glycogen synthase kinase‐3) causes tau dephosphorylation at the sites recognized by antibodies Tau‐1 and PHF‐1 both in cultured neurons and in vivo in rat brain. This is consistent with a major role for glycogen synthase kinase‐3 in modifying proline‐directed sites on tau protein within living neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
184
0
5

Year Published

1999
1999
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 300 publications
(195 citation statements)
references
References 40 publications
(42 reference statements)
6
184
0
5
Order By: Relevance
“…118 Although many of the studies have utilized lithium concentrations in excess of those utilized therapeutically, the available data suggest that lithium, at concentrations of ෂ1 mM does, indeed, reduce tau phosphorylation. 118,[123][124][125] Overall, the data suggest that in addition to bcl-2 upregulation, inhibition of GSK-3␤ by lithium may also afford protection against the cell death induced by various stimuli. 126 In view of the important role of GSK-3␤ in cell survival, a study was undertaken to determine if other mood stabilizers also regulate GSK3␤.…”
Section: Inhibition Of Glycogen Synthase Kinase 3␤ (Gsk-3␤) May Also mentioning
confidence: 90%
“…118 Although many of the studies have utilized lithium concentrations in excess of those utilized therapeutically, the available data suggest that lithium, at concentrations of ෂ1 mM does, indeed, reduce tau phosphorylation. 118,[123][124][125] Overall, the data suggest that in addition to bcl-2 upregulation, inhibition of GSK-3␤ by lithium may also afford protection against the cell death induced by various stimuli. 126 In view of the important role of GSK-3␤ in cell survival, a study was undertaken to determine if other mood stabilizers also regulate GSK3␤.…”
Section: Inhibition Of Glycogen Synthase Kinase 3␤ (Gsk-3␤) May Also mentioning
confidence: 90%
“…121 Tau has been identified as an important substrate of GSK-3 in vitro and in vivo and can be phosphorylated at primed (e.g., T231) and unprimed epitopes (PHF-1, Tau-1, and AT8). [122][123][124] Priming involves the prior phosphorylation of a serine or threonine residue, four amino acids C-terminal to the target phosphorylation site. 125 Active GSK-3 was detected in pretangle neurons and NFTs in AD brains, and coexpression of the GSK-3 homolog shaggy with tau led to tau hyperphosphorylation, filamentous tau aggregation, and neurotoxicity in Drosophila fruit fly.…”
Section: Antiphosphorylation Strategiesmentioning
confidence: 99%
“…60 In addition, GSK-mediated phosphorylation of MAP-B and tau proteins regulate microtubule assembly and stabilization at synapses. 57,[61][62][63] Clinical studies have demonstrated that specific GSK-3 inhibitors mimic the therapeutic action of mood stabilizers and might therefore be plausible drugs in treating bipolar patients. 64 Crosstalk between PKC and GSK-3b signaling pathways Certain PKC isoforms have been shown to phosphorylate and inactivate GSK-3b in vitro.…”
Section: Lithium and Wnt Signaling Pathwaymentioning
confidence: 99%